Compaction of Single-Molecule Megabase-Long Chromatin under the Influence of Macromolecular Crowding - Zinchenko, Anatoly; Berezhnoy, Nikolay V.; Chen, Qinming; Nordenskiöld, Lars (Biophysical journal, 2018)
The megabase-sized length of chromatin is highly relevant to the state of chromatin in vivo, where it is subject to a highly crowded environment and is organized in topologically associating domains of similar dimension. We developed an in vitro experimental chromatin model system reconstituted from T4 DNA (approximately 166 kbp) and histone octamers and studied the monomolecular compaction of this megabase-sized chromatin fiber under the influence of macromolecular crowding. We used single-molecule fluorescence microscopy and observed compaction in aqueous solutions containing poly(ethylene glycol) in the presence of monovalent (Na+ and K+) and divalent (Mg2+) cations. Both DNA and chromatin demonstrated compaction under comparable conditions in the presence of poly(ethylene glycol) and Na+ or Mg2+ salt. However, the mechanism of the compaction changed from a first-order phase transition for DNA to a continuous folding for megabase-sized chromatin fibers. A more efficient and pronounced chromatin compaction was observed in the presence of Na+ compared to K+. A flow-stretching technique to unfold DNA and chromatin coils was used to gain further insight into the morphology of partially folded chromatin fibers. The results revealed a distribution of partially folded chromatin fibers. This variability is likely the result of the heterogeneous distribution of nucleosomes on the DNA chain. The packaging of DNA in the form of chromatin in the crowded nuclear environment appears essential to ensure gradual conformational changes of DNA.